A Supramolecular Interaction of a Ruthenium Complex With Calf-Thymus DNA: A Ligand Binding Approach by NMR Spectroscopy - Kock, Flávio Vinícius Crizóstomo; Costa, Analu Rocha; de Oliveira, Katia Mara; Batista, Alzir Azevedo; Ferreira, Antônio Gilberto; Venâncio, Tiago (Frontiers in Chemistry, 2019)
Lawsone itself exhibits interesting biological activities, and its complexation with a metal center can improve the potency. In this context a cytotoxic Ru-complex, [Ru(law)(dppb)(bipy)] (law = lawsone, dppb = 1,4-bis(diphenylphosphino)butane and bipy = 2,2`-bipyridine), named as CBLAU, was prepared as reported. In this work, NMR binding-target studies were performed to bring to light the most accessible interaction sites of this Ru-complex towards Calf-Thymus DNA (CT-DNA, used as a model), in a similar approach used for other metallic complexes with anticancer activity, such as cisplatin and carboplatin. Advanced and robust NMR binding-target studies, among them Saturation Transfer Difference (STD)-NMR and longitudinal relaxometry (T1), were explored. The 1H and 31P -NMR data indicate that the structure of Ru-complex remains preserved in the presence of CT-DNA, and some linewidth broadening is also observed for all the signals, pointing out some interaction. Looking at the binding efficiency, the T1 values are highly influenced by the formation of the CBLAU-DNA adduct, decreasing from 11.4 s (without DNA) to 1.4 s (with DNA), where the difference is bigger for the lawsone protons. Besides, the STD-NMR titration experiments revealed a stronger interaction (KD = 5.9 mM) for CBLAU-DNA in comparison to non-complexed lawsone-DNA (KD = 34.0 mM). The epitope map, obtained by STD-NMR, shows that aromatic protons from the complexed lawsone exhibits higher saturation transfer, in comparison to other Ru-ligands (DPPB and bipy), suggesting the supramolecular contact with CT-DNA takes place by the lawsone face of the Ru-complex, possibly by a spatial π-π stacking involving π-bonds on nucleic acids segments of the DNA chain and the naphthoquinone group.